Adopting Word Processor Tools to Overcome Post-Graduate Students’ Challenges in Academic Writing - Siti Drivoka Sulistyaningrum (UNIB Press, 2024)
The emergence of word-processing software assisted students in overcoming academic writing challenges. Other research, however, revealed that it was more concerned with students' academic writing challenges in linguistic problems than with how to handle them using a word processor. As a result, the purpose of this study is to determine how to adopt word processor features to assist postgraduate students who have problems with academic writing. As the study design, a qualitative survey with descriptive analysis was employed. Students' article writing and 10 second-semester postgraduate students from January until June 2023 enrolled in an Academic writing course at one of the universities in Jakarta and served as data sources. Data were gathered through the analysis of students' article writing and an online questionnaire, which were then analysed and interpreted descriptively. This research revealed that word class was discovered to be the most challenging, followed by word mistakes, grammar, and word format in the classroom. It was discovered that using a word processor might assist them the most in overcoming word formatting challenges, followed by spelling errors, grammar, and word classes. As a result, despite the extensive use of word processing tools, students should not abandon reading while writing academically with this tool because it cannot guarantee that it will aid them 100% of the time.